You need to identify the term that contains the variable x and let it alone to one side, by moving the constant member to the other side, such that:

`2x = -6 - (-8)`

Performing the multiplication -`1*(-8)` converts the negative 8 into positive 8, such that:

`2x = -6 + 8 => 2x = 2 `

Reducing duplicate factors yields:

`x = 1`

**Hence, evaluating the solution to two steps equation yields **`x = 1.`

The aim of any equation is to find out the value or values of the variable that cancel the given expression.

The first step is to re-write -(-8) = 8. The double negative sign makes a value positive.

2x + 6 = 8

Now, we'll subtract 6 both sides in order to isolate the variable x to the left side:

2x = 8 - 6

2x = 2

Now, we'll divide by 2 and we'll get:

x = 2/2

x = 1

So, the solution of the equation is x = 1.

We'll verify the solution into equation, substituting the variable by the value 1:

2*1 + 6 = 8

2 + 6 = 8

8 = 8

So, the solution is x = 1.